2018
DOI: 10.1155/2018/9589472
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of α‐Glucosidase, Intestinal Glucose Absorption, and Antidiabetic Properties by Caralluma europaea

Abstract: Many medicinal plants around the world are used for therapeutic purposes against several diseases, including diabetes mellitus. Due to their composition of natural substances that are effective and do not represent side effects for users, unlike synthetic drugs, in this study, we investigated the inhibitory effect of Caralluma europaea (CE) on α-glucosidase activity in vitro; then the kinetics of the enzyme were studied with increasing concentrations of sucrose in order to determine the inhibition type of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 42 publications
0
28
0
1
Order By: Relevance
“…α-Amylase and α-glucosidase are considered as key therapeutic targets for the management of type II diabetes. α-Amylase and α-glucosidase are carbohydrate hydrolysing enzymes, responsible for the breakdown of carbohydrates into glucose [35,36]. The present study showed that all ATP and ACT extracts displayed weak α-amylase inhibitory effects, despite being active α-glucosidase inhibitors.…”
Section: Resultsmentioning
confidence: 56%
“…α-Amylase and α-glucosidase are considered as key therapeutic targets for the management of type II diabetes. α-Amylase and α-glucosidase are carbohydrate hydrolysing enzymes, responsible for the breakdown of carbohydrates into glucose [35,36]. The present study showed that all ATP and ACT extracts displayed weak α-amylase inhibitory effects, despite being active α-glucosidase inhibitors.…”
Section: Resultsmentioning
confidence: 56%
“…However, rats treated with AECe + CCl 4 showed a significant reduction in plasma glucose concentration in comparison with the CCl 4 -treated group. In our investigation, AECe could enhance insulin secretion and stimulate the storage of glucose by the peripheral glucose uptake [ 19 ]. For the lipid profile, the serum levels of triglyceride and VLDL-c showed remarkable increases in CCl 4 -treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…The aqueous extract of C. europaea was administered at a single dose of 250 mg/kg. The dose of the aqueous extract of C. europaea (250 mg/kg) was selected based on the previous efficacy studies (acute and subacute toxicity studies and many previous pharmacological activities of C. europaea ) [ 19 , 26 ]. Silymarin (40 mg/kg) was administered to the animals orally [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of the ODSO against intestinal α-glucosidase activity was quantified colorimetrically by monitoring the d -glucose release from sucrose degradation, according to the protocol described by Ouassou et al [ 80 ], with some modifications. The assay mixtures contained 100 μL of sucrose (50 Mm), 1000 μL of phosphate buffer (50 mM; pH = 7.5), and 100 μL of intestinal α-glucosidase enzyme solution (10 IU).…”
Section: Methodsmentioning
confidence: 99%